ANALISIS PLOIDI PLANTLET ANGGREK TANAH HIBRID (Spathoglottis x Bintang Segunung) HASIL KULTUR OVARIUM SECARA IN-VITRO - , AGUS SETIAWAN; , Dr. Budi Setiadi Daryono, M.Agr.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A rapid and efficient micropropagation method was esthablished for produced Orchid Hybrid Spathoglottis x Bintang Segunung from Indonesia. The aim of this research was to optimize effects of 2,4-Dichlorophenoxyacetic acid (2,4-D), cold shock, and 6-Benzylaminopurine (BAP) to plantlet regeneration from ovarium culture and analyse the ploidy using flow cytometry. Ovarium explants from anthesis flower stalk were cultured on Vacin and Went (VW) medium supplemented with 2,4-D at 5 concentrations (0.01-1 ppm) and cold shock treatment after cultured at 3 variations 10oC (0, 2, and 4 h) and then incubate the explants in room with 24 photoperiodization (Â±25oC). After 10 days, while ovarium explants were subcultured on VW supplemented with 6-benzylaminopurin (BAP) at 5 concentrations 0.5-2.5 ppm until 2 weeks. Further, ovarium explants were subcultured again on VW medium with filtered coconut water (150 ml/L). Regeneration of protocorm-like bodies (PLBs) and subsequent plantlet development were observed from on VW+ 1 ppm 2,4-D (Sig= 2%)+ 4h cold shock 10oC (Sig= 2%) dan 2,5 ppm BAP (Sig= 0,62%). The optimized procedure required about 2 months from cultured of the ovarium explant to plantlet formation. The peak from the histogram of flow cytometry showed that ovarium cultured of S. x Bintang Segunung (CV= 4,35%) and leave of S. x Bintang Segunung (CV= 5,19%) were the same triploid. The protocol of this experiment could produce the uniform plantlets and expected to initiate the regeneration of ovul cell which need more studying for the medium optimation.